2021
DOI: 10.3390/cryst11070754
|View full text |Cite
|
Sign up to set email alerts
|

A Constitutive Relation Based on the Johnson–Cook Model for Ti-22Al-23Nb-2(Mo, Zr) Alloy at Elevated Temperature

Abstract: Although several schemes have been proposed to modify the classical Johnson–Cook (J-C) model, the effect of temperature on the flow stress of materials at different temperatures has not been clarified. In the current study, to investigate the deformation behavior of Ti-22Al-23Nb-2(Mo, Zr) alloy at different temperatures, uniaxial tension experiments were performed at both room (RT, 28 °C) and elevated temperatures, and a modified J-C model was developed to describe the temperature-dependent plastic flow. In te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…He et al [ 23 , 24 ] illustrated that the dynamic flow stress of Ti 2 AlNb is sensitive to the competition of the thermal softening effect with strain rate hardening effect. Wang et al [ 25 ] conducted the uniaxial tension experiments of hot-rolled Ti-22Al-23Nb-2(Mo, Zr) alloys at both room (RT, 28 °C) and elevated temperatures (500, 550, and 650 °C). They found that the peak stress was significantly relevant to the test temperature.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [ 23 , 24 ] illustrated that the dynamic flow stress of Ti 2 AlNb is sensitive to the competition of the thermal softening effect with strain rate hardening effect. Wang et al [ 25 ] conducted the uniaxial tension experiments of hot-rolled Ti-22Al-23Nb-2(Mo, Zr) alloys at both room (RT, 28 °C) and elevated temperatures (500, 550, and 650 °C). They found that the peak stress was significantly relevant to the test temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Qian et al [12] proposed a modified Johnson-Cook model considering the coupled effects of strain, strain rate and temperature on the behaviour of the material, which can give an accurate and credible prediction of the dynamic behaviour of the CuCrZr alloy over a wide range of strain rates and temperatures. Wang et al [13] proposed the modified Johnson-Cook model by introducing high-temperature softening parameters, which can correctly describe the deformation behaviour at any temperature within a specific range. Yang et al [14] proposed the strain-modified Arrhenius constitutive equation for 20MnCr5, which has strong prediction ability, and provided the temperature and strain rate interval to avoid its plastic instability.…”
Section: Introductionmentioning
confidence: 99%
“…These results accurately describe the high-temperature deformation behaviors of the alloy. Wang et al [15] proposed a modified J-C constitutive model to exactly represent the flow stress behavior of Ti-22Al-23Nb-2(Mo, Zr) alloy. Zhao et al [16] studied the high-temperature deformation behavior of ingot metallurgy Ti-5V-5Mo-3Cr-5Al alloy via a processing map.…”
Section: Introductionmentioning
confidence: 99%